Malignant epitheliod hemangioendothelioma of the thyroid: a case report - França, Mariana M. [UNESP]; Souza, Gregório L. [UNESP]; Frank, Michell [UNESP]; Fabris, Viciany Erique [UNESP]; Tagliarini, José Vicente [UNESP]; Mazeto, Gláucia [UNESP] (My University, 2011)
Primary malignant epithelioid hemangioendothelioma (MEH) of the thyroid is a rare neoplasia with only a few cases reported in the literature. We report a 75 year old man, who presented with a substernal goiter and compressive symptoms. Ultrasonographic evaluation revealed a hypoechogenic nodule in the left lobe, measuring 4.1 cm in maximum diameter, and associated gross calcifications. Fine needle aspiration yielded hemorrhagic material. A left thyroid lobectomy and isthmusectomy was performed. The surgical specimen contained a malignant epithelioid hemangioendothelioma measuring 6 x 4 x 3 cm that had infiltrated about 50% of the thyroidal parenchyma, and surrounded a necrotic nodule. Immunohistochemistry results corroborated the histopathological findings; staining was positive for AE1/AE3, CD31, CD34, factor VIII-related antigen, and Ki-67 expression. Because of the patient’s comorbidities, surgical complementation was not undertaken and he has been undergoing conservative treatment.
Keywords: Thyroid nodules; Hemangioendothelioma; Goiter; Rare neoplasia